Domestic violence victimization among Chinese women and its relevance to their economic power - Wang, Zixuan; Sekiyama, Takashi (Frontiers in Sociology, 2023)
Introduction This study conducted a survey of domestic violence victimization among women in China. Previously little research has been conducted on the subject of domestic violence against Chinese women as well as its relevance to their own economic power. Methods Using online questionnaires, this study collected data about 412 women with current or previous marital status who came from four income brackets in Beijing and Shanghai. Results It revealed that the proportions of physical, emotional, economic, and sexual violence they experienced were about 27.91%, 62.38%, 21.12%, and 30.10%, respectively. Women belonging to the highest income bracket faced almost the same risk of domestic violence compared with other income groups. Furthermore, there was a slight upward tendency in physical and emotional violence victimization in the highest-income group. The binary logistic regression analysis showed that adverse childhood experiences, arguments between couples due to different opinions regarding gender ideologies, and the approval level for specific gender ideologies were common significant factors across different income brackets. When all income brackets were considered, a higher income was tested as a protective factor with regard to sexual violence. As for the income gap between couples, women whose incomes were “once higher than that of the husband but now lower/almost the same” or “always higher than that of the husband” faced a higher risk of physical violence than women whose incomes were “always lower than/almost the same as that of the husband.” Discussion This study not only revealed the reality of domestic violence victimization in China but also suggested that more attention should be paid to high-income women's domestic violence victimization as well as the importance of helping them both through academia and domestic violence support institutions.